WORKSHOP OWNER'S RESPONSIBILITY FOR MOTORCYCLE DAMAGES AFTER REPAIR: WAHBAH AZ-ZUHAILI'S PERSPECTIVE CASE STUDY OF NORTH PADANG LAWAS REGENCY, PADANG BOLAK DISTRICT - Ilfendri Muda; Rahmad Efendi (Journal Analytica Islamica, 2026)
This study examines the liability of workshop owners for motorcycle damage after repair services in Padang Bolak Subdistrict, North Padang Lawas Regency, and analyzes it through the perspective of Wahbah az-Zuhaili’s Islamic legal thought. The research responds to the gap between normative consumer protection regulations and empirical practices in small-scale repair services. Using an empirical legal approach with qualitative analysis, data were collected through in-depth interviews, observation, and documentation, then examined in light of Indonesian Consumer Protection Law and the fiqh concept of ijarah and dhaman. The findings reveal that workshop owners’ liability has not been implemented adequately. Most workshop owners avoid providing compensation or re-repair services even when post-repair damage is linked to technical negligence. This condition is influenced by limited legal awareness, economic constraints, and weak professional ethics. From Wahbah az-Zuhaili’s perspective, repair services constitute an ijarah contract grounded in trust (amanah) and liability (dhaman). Any negligence resulting in loss obliges the service provider to bear responsibility under the principle of al-ghurm bil ghunm. This study contributes theoretically by integrating empirical consumer protection issues with contemporary Islamic legal doctrine, demonstrating that liability in service transactions is not merely a legal obligation under national law but also a binding moral and sharia obligation. Practically, the findings highlight the need to strengthen legal literacy and ethical awareness among service providers to ensure fair and accountable consumer protection.